2009
DOI: 10.1007/s11096-009-9336-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacy services in an Iranian teaching hospital: a descriptive study

Abstract: These results support the importance of clinical pharmacists' participation in health care team rounds to improve the overall quality of medication therapy, enhance patient care and outcome and reduce drug costs to patients and society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…Thanks to the evolution of clinical pharmacy in Iran and the increased cooperation of clinical pharmacists in multidisciplinary team, they have played a beneficial role in implementing new services to address various problems in different clinical settings such as infectious diseases wards [17][18][19]. Controlling blood glucose is difficult in hospitalized patients especially among those with infectious diseases [20].…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to the evolution of clinical pharmacy in Iran and the increased cooperation of clinical pharmacists in multidisciplinary team, they have played a beneficial role in implementing new services to address various problems in different clinical settings such as infectious diseases wards [17][18][19]. Controlling blood glucose is difficult in hospitalized patients especially among those with infectious diseases [20].…”
Section: Discussionmentioning
confidence: 99%
“…We were not able to identify any adequate study from developing countries reporting TRPs or the impact of proper clinical pharmacy service on hospitalized patients. We have identified only few reports of very small sample size or studies describing limited or disease specific clinical pharmacy service [34][35][36][37][38]. The main aim of the current study was to identify the prevalence and characteristics of TRPs in hospitalized internal medicine patients in Jordan.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown the benefit of pharmacist's interventions in improving patients' outcomes by involving in the health care team rounds, interviewing patients, reconciling medications, and providing patient discharge counseling and follow-up [6][7][8][9][10][11][12]. Clinical pharmacists actively participated in medical treatment team in the teaching hospitals in Iran.…”
Section: Discussionmentioning
confidence: 99%